국내 돼지풀(Ambrosia artemisiifolia L.) 집단의 유전적 다양성 - 허경종(Gyeong-Jong Huh); 김진원(Jin-Won Kim) (Weed & turfgrass science, 2023)
돼지풀(Ambrosia artemisiifolia L.)은 생태계교란생물로 일반생태계를 교란할 뿐 아니라, 농업생산량을 감소시키는 주요 잡초 중 하나이다. 돼지풀에 대한 화학적 방제법은 개발되었으나 발생장소에 따라 제초제 사용에 제한이 있다. 따라서, 광범위하게 사용할 수 있는 생물학적 방제법 수립의 기초정보를 제공하고자 EST-SSR마커 7종 및 신규개발 SSR마커 8종을 이용하여 국내 돼지풀 5집단에 대한 유전적 다형성 및 다양성을 평가하였다. 그 결과, 유전적 다양성은 감소하고 있지만, 집단 내부의 유전적 다양성은 아직 높은 수준을 유지하는 것으로 분석되었다. 이는 돼지풀의 자가불화합성특성에 기인하고 있으며, 현재 집단간 유전적 교류가 줄어들고 있음을 시사한다. 주성분분석 결과, 사천과 대구 집단을제외한 국내 돼지풀 집단은 극동러시아 집단과 유전적으로 가까운 것으로 분석되어 상호 연관성이 있다고 추측되었다 Common ragweed (Ambrosia artemisiifolia ) is one of the Invasive Alien Species in the Republic of Korea; and is one of the major weeds in the upland crop. Polymorphism and genetic diversity among 5 populations collected from the Republic of Korea, were investigated by using 7 EST-SSR markers and 8 newly-developed SSR markers. As a result, the general genetic diversity of A. artemisiifolia would have been slowly decreased, and intra-population genetic diversity, however, would have been maintained at a high level. The results suggest that gene flow between A. artemisiifolia populations in the Republic of Korea could be limited. As a result of principal coordinates analysis, some populations grouped with Far-East Russian populations suggesting that the Koreans and the Russians might be genetically related. KCI Citation Count: 0